Evaluasi Kebijakan Penggunaan Aplikasi Sakti Pada Direktorat Jenderal Perbendaharaan Dalam Rangka Meningkatan Kualitas Laporan Keuangan - Punarto, Novang Tendy; Irawan, Bambang (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
This research aims to evaluate the policy of using the SAKTI Application (Sistem Aplikasi Keuangan Tingkat Instansi) at the Head Office of the Directorate General of Treasury in an effort to improve the quality of financial reports. Accurate and high-quality financial reports are an essential component in realizing accountability and transparency in state financial management. The Sakti Application is expected to help minimize errors and inconsistencies in financial reporting by providing an integrated system, data validation, audit trails, and process standardization. This research uses a qualitative method by collecting data through in-depth interviews with key stakeholders, field observations, and documentation studies. The evaluation is carried out using criteria developed by William N. Dunn (2021:610), including effectiveness, efficiency, adequacy, equity, responsiveness, and policy appropriateness. Based on the research results, it shows that the policy of using the Sakti Application has met the criteria of effectiveness, efficiency, adequacy, equity, responsiveness, and policy appropriateness and has made a positive contribution to improving the quality of financial reports, but there are still obstacles that need to be resolved. The proposed suggestions include improving IT infrastructure, providing complaint facilities, continuous training, and enhancing data security.